Problems in publication of results of scientific research, their visibility and possible frauds - Živković Živan (Trendovi u Poslovanju)
This paper presents the results of the research on the basic motivation of people to engage in scientific research and publication of the obtained results. The main problems regarding mentioned activities which occur today are manifested in the emergence of numerous frauds in the form of plagiarism, autoplagiarism, false publications and predatory publications. The most important purpose of publishing the scientific and research results is achieving their visibility. Visibility of a published result enables a critical review of its merits by other researchers through the utilization of the published results for the purpose of further research, i.e. their citation, which represents the most reliable criterion for measuring the quality of the published result. In this paper a comparative analysis of the most famous citation databases is presented which include Google Scholar Metrics (GSM), Clarivate Journal Citation Reports (JCR), SCimago Journal Ranking (SJR), Web of Science and Elsevier's SCOPUS database, in which the ranking of the quality of scientific publications is based on the so-called impact factor (IF). Furthermore, a very popular h-index is also described as an indicator of the results achieved by a particular researcher.